Peran Kepemimpinan Kiai dalam Penguatan Identitas Keagamaan di Komunitas Muslim Perkotaan - Nisa, Akramun; Andy, Andy (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
This study examines the role of kiai leadership in strengthening the religious identity of urban Muslim communities, specifically at Pesantren Darul Falah Ternate. In an urban context, modernization and globalization often pose challenges that erode religious values in society. The kiai at Pesantren Darul Falah serves as a spiritual leader and a figure who preserves the continuity of Islamic values within the increasingly pluralistic and dynamic urban environment. This research aims to understand how the Kiai face these challenges and maintain the religious identity of the Muslim community. This study employs a descriptive qualitative method with observation, interviews, and document analysis. Data were analyzed using the methods of Miles, Huberman, and Saldana through data condensation and presentation in narrative form to highlight relevant information. The research findings show that the Kiai's leadership at Pesantren Darul Falah successfully maintained religious identity through religious activities such as study groups, zikr, and sermons and through collaboration with the government and local communities. The Kiai also utilized modern technology to disseminate Islamic teachings, bridging religious traditions with modern life. Furthermore, strategic partnerships with various parties have strengthened the role of the pesantren as a center for social and economic empowerment. These findings emphasize the importance of the adaptive and collaborative role of the kiai in addressing social changes.